Macroeconomic Variables Influence on Stock Market Performance - Norazidah, Shamsudin; Mohd Izuan, Rosmi; Suhana, Mohamed (Human Resource Management Academic Research Society (HRMARS), 2021)
Investors should consider stock market performance when making an investment decision. Both economic and non-economic factors influence the stock market's performance. Previous research, primarily from developed markets, has revealed that macroeconomic factors significantly impact stock returns. Economic forces are used in this paper to investigate the significant relationship between selected macroeconomic variables, the Malaysian stock return index for the financial sector, and the Bursa Malaysia Finance Services Index. The macroeconomic variables examined are inflation (INF), money supply (M.S.) and the real effective exchange rate (REER). This study's sample consists of 164 time-series observations. The observations are annual secondary data obtained from the World Bank, Index Mundi, and the Malaysian Bureau of Statistics from January 1979 to December 2019. Several regression analyses and econometric tests were performed with the interactive software package E-Views 11. The findings of this research paper provide an initial overview and can serve as a valuable foundation for investors' and policymakers' respective investment strategies and policies.